2013
DOI: 10.14202/vetworld.2013.674-680
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of live gumboro vaccine prepared from local variant strain for control of infectious bursal disease in Egypt

Abstract: Aim: The present study was designed to evaluate live Gumboro (IBD) vaccine prepared from local variant isolated strain (Egy-IBD Var 2009 Vp2 gene-, partial cds submitted in gen bank at accession no. : JN 118617) for controlling IBD problem in Egypt. Material and Methods: Local isolated variant strain was adapted on Baby Grivet Monkey kidney cell line -70(BGM-70) 7.5 4.5 used for preparation of tissue culture (T.C) live vaccine. T.C IBDV had a titer of 10 TCID /ml (10 TCID per dose) after 50 50five passages in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A study done in Bangladesh to compare isolation of IBDV using commercial hybrid chicken embryos and indigenous chicken embryos [ 15 ] showed that rural indigenous chicken eggs were better for virus isolation than commercial farm hybrid chicken eggs. Strains of IBDV circulating in North Africa [ 16 , 17 ] and West Africa [ 18 ] have been isolated for characterization and vaccine development but not in East Africa. Currently, there is no report available on isolation of local IBDV strains using embryonated indigenous chicken eggs in Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…A study done in Bangladesh to compare isolation of IBDV using commercial hybrid chicken embryos and indigenous chicken embryos [ 15 ] showed that rural indigenous chicken eggs were better for virus isolation than commercial farm hybrid chicken eggs. Strains of IBDV circulating in North Africa [ 16 , 17 ] and West Africa [ 18 ] have been isolated for characterization and vaccine development but not in East Africa. Currently, there is no report available on isolation of local IBDV strains using embryonated indigenous chicken eggs in Kenya.…”
Section: Introductionmentioning
confidence: 99%